Chinese yuan interest rate swap yields - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2023)
This paper models the dynamics of Chinese yuan (CNY)-denominated long-term interest rate swap yields. The financial sector plays a vital role in the Chinese economy, which has grown rapidly in the past several decades. Going forward, interest rate swaps are likely to have an important role in the Chinese financial system. This paper shows that the short-term interest rate exerts a decisive influence on the long-term swap yield after controlling for various macrofinancial variables, such as inflation or core inflation, the growth of industrial production, percent change in the equity price index, and the percentage change in the CNY exchange rate. The autoregressive distributed lag (ARDL) approach is applied to model the dynamics of the long-term swap yield. The empirical findings show that the People's Bank of China's influence extends even to the over-the-counter derivative products, such as CNY interest rate swap yields, through the short-term interest rate. The findings reinforce and extend John Maynard Keynes's notion that the central bank's actions have a decisive role in setting the long-term interest rate in emerging market economies, such as China.
Keywords: E43; E50; E60; G10; G12; 330; Chinese Yuan (CNY) Swaps; Interest Rate Swaps; Short-Term Interest Rate; Monetary Policy; The People's Bank of China (PBOC)